2019
DOI: 10.1136/bjophthalmol-2019-314913
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular foreign body injury in children: clinical characteristics and factors associated with endophthalmitis

Abstract: Background/AimsTo analyse the clinical characteristics of intraocular foreign body (IOFB) injury in children and evaluate factors associated with endophthalmitis development.MethodsPatients aged <18 years with IOFB attending Zhongshan Ophthalmic Center between January 2003 and July 2016 were included retrospectively. Demographic features, clinical characteristics and factors associated with endophthalmitis development were analysed.ResultsConsecutive subjects (n=484, 484 eyes) were included: mean age 10.12±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
2
14
1
2
Order By: Relevance
“…Similarly, our study found that over 85% of injuries occurred at home were mostly self-inflicted, and that scissors were the leading cause of injuries (28.6%). Zone I was the most common wound entry site, and traumatic cataract presented as the common sign in our study, consistent with previous studies on paediatric post-traumatic endophthalmitis [ 1 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, our study found that over 85% of injuries occurred at home were mostly self-inflicted, and that scissors were the leading cause of injuries (28.6%). Zone I was the most common wound entry site, and traumatic cataract presented as the common sign in our study, consistent with previous studies on paediatric post-traumatic endophthalmitis [ 1 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on paediatric ocular trauma found that the proportion of males was close to that of females in younger children and increased with age [ 19 21 ]. Preschool patients aged 0–6 years were included in our study, and the proportion of males was close to that of females (57.1% vs. 42.9%), consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportion of posttraumatic endophthalmitis (85.0%) among children was much higher than adult-dominated population reported from the same region (58.0-58.5%) [15,23]. The higher proportion of traumatic endophthalmitis in the pediatric population could be explained by that fact that children are generally unable to either recognize or explain their symptoms after injury, thereby resulting in delayed presentation and treatment, leading to a higher incidence of endophthalmitis [24].…”
Section: Discussioncontrasting
confidence: 51%
“…Intraocular cilium have been reported to be asymptomatic for 50 year in the anterior chamber [ 11 ]. However, more reports have shown that cilia left in eyes tend to cause polytype endophthalmitis [ 1 , 2 ]. Therefore, the cilia, especially with follicle found accidentally in the operation, should be taken out at the same time if possible.…”
Section: Discussionmentioning
confidence: 99%
“…An intraocular foreign body is present in 18–41% of open-globe injuries [ 1 ] and is the key factor for visual outcome when removing an intraocular foreign body. Cilia is a type of small autogenic biological intraocular foreign body that is difficult to detect by auxiliary equipment prior to surgery, especially when located at the posterior ocular segment [ 2 ], and can lead to infective endophthalmitis or uveitis [ 3 ]. It was also a key factor leading to intraocular infection after intraocular foreign body removal surgery.…”
Section: Introductionmentioning
confidence: 99%